PHENOMENA BEHAVIOR FRAUD IN GOVERNMENT - Mardatillah, Mardatillah; Irianto, Jusuf; Mariyanta, Antun (Universitas Brawijaya, Indonesia, 2020)
This research is based on government civil state apparatus as the government's front guard that reflects the healthy and strong government but the facts showed that there are cases of government doing fraudulent behavior from mild to severe. Also, it aims to reveal the phenomenon of fraud behavior of the civil apparatus. This is the preliminary research obtained from interviews and observation in the field by actively participating in every government activity. The result of the research shows that the mild cheating fraud behavior in each unit of the regional apparatus is handled by the superior of the agency and they only make a report of doing coaching to the employment agency and the human resource development. For the medium and heavy fraud behavior, the coaching is done by the employment agency and human resource development together with the inspectorate agency by making a coaching team. Coaching is done based on complaints from the number of Regional Work Unit (SKPD), community complaints, and monthly attendance monitoring. The phenomenon of fraud behavior in the government environment. Furthermore, the results of this study can act also as consideration matters to change the system, procedures, and policies to prevent fraud behavior and suppress the culture. For further researchers to make a comparison of methods and mix methods also find the factors that cause and prevent potential violations